The first gentleman : a thriller - Clinton, Bill, 1946-; Patterson, James, 1947- (Little, Brown and Company, Hachette Book Group ; Alfred A. Knopf, 2025)
"The President of the United States is up for reelection. Her husband is on trial for murder. Is the First Gentleman a killer? A pair of brilliant investigative journalists set out to answer that burning question about the NFL star-turned-political spouse"--